Recent advances and prospects in purification and heterologous expression of lactoferrin. Issue 1 (25th March 2022) - Cui, Shixiu; Lv, Xueqin; Sun, Guoyun; Wu, Wenyang; Xu, Hong; Li, Yuelong; Liu, Yanfeng; Li, Jianghua; Du, Guocheng; Wang, Miao; Liu, Long
Abstract: Lactoferrin is an 80 kDa iron‐binding glycoprotein of the transferrin family, which is abundant in milk and in most biological fluids. Besides the direct antimicrobial properties, lactoferrin can regulate immune responses and prevent infection and septic shock. Membrane adsorption and chromatographic methods are usually used for separating and purifying of lactoferrin from bovine milk. However, the content of lactoferrin in milk is relatively low, resulting in a high cost of producing lactoferrin. Meanwhile, as a heterologous protein applied to the human body, it may cause a certain antigen response. Therefore, obtaining a large amount of biologically active lactoferrin has always been a research hot topic. This review first introduced the physical and chemical properties, and biological activities of lactoferrin. Then, the current recombinant expression systems for lactoferrin were summarized. Finally, the current challenges and the future development trends of efficient synthesis of lactoferrin were discussed. Abstract : Lactoferrin has a wide range of biological roles. Different expression systems have been developed for the synthesis of lactoferrin, including bacteria, yeast, filamentous fungi, animal cells, and cell‐free protein synthesis, and the main expression elements and processes of each expression system are shown.